Existence of solutions for a nonlinear problem at resonance - Haddaoui Mustapha; Lebrimchi Hafid; Ouhamou Brahim; Tsouli Najib (Demonstratio Mathematica, 2022)
In this work, we are interested at the existence of nontrivial solutions for a nonlinear elliptic problem with resonance part and nonlinear boundary conditions. Our approach is variational and is based on the well-known Landesman-Laser-type conditions.